The Australian approach to geospatial capabilities; positioning, earth observation, infrastructure and analytics: issues, trends and perspectives. Issue 2 (3rd April 2017) - Woodgate, Peter; Coppa, Isabel; Choy, Suelynn; Phinn, Stuart; Arnold, Lesley; Duckham, Matt
Abstract: This paper examines the current state of three of the key areas of geospatial science in Australia: positioning; earth observation (EO); and spatial infrastructures. The paper discusses the limitations and challenges that will shape the development of these three areas of geospatial science over the next decade and then profiles what each may look like in about 2026. Australia's national positioning infrastructure plan is guiding the development of a nation-wide, sub decimeter, real-time, outdoor positioning capability based on multi-GNSS and in particular the emerging precise point positioning − real-time kinematic (PPP-RTK) capability. Additional positioning systems including the ground-based Locata system, location-based indoor systems, and beacons, among others are also discussed. The importance of the underpinning role of a next generation dynamic datum is considered. The development of Australia's first EO strategy is described along with the key national needs of the products of remote sensing. The development of massive on-line multi-decadal geospatial imagery data stores and processing engines for co-registered stacks of continuous base-line satellite imagery are explored. Finally, perspectives on the evolution of a future spatial knowledge infrastructure (SKI) emerging from today's traditional spatial data infrastructures (SDIs) are provided together with discussion of the growing importance of geospatial analytics for transforming whole supply chains.